Adrenomedullin and endothelin-1 are associated with myocardial injury and death in septic shock patients. Issue 1 (December 2016) - Lundberg, Oscar; Bergenzaun, Lill; Rydén, Jörgen; Rosenqvist, Mari; Melander, Olle; Chew, Michelle
Abstract Background Adrenomedullin and endothelin-1 are hormones with opposing effects on the cardiovascular system. Adrenomedullin acts as a vasodilator and seems to be important for the initiation and continuation of the hyperdynamic circulatory response in sepsis. Endothelin-1 is a vasoconstrictor and has been linked to decreased cardiac performance. Few studies have studied the relationship between adrenomedullin and endothelin-1, and morbidity and mortality in septic shock patients. High-sensitivity troponin T (hsTNT) is normally used to diagnose acute cardiac injury but is also prognostic for outcome in intensive care. We investigated the relationship between mid-regional pro-adrenomedullin (MR-proADM), C-terminal pro-endothelin-1 (CT-proET-1), and myocardial injury, measured using transthoracic echocardiography and hsTNT in septic shock patients. We were also interested in the development of different biomarkers throughout the ICU stay, and how early measurements were related to mortality. Further, we assessed if a positive biomarker panel, consisting of MR-proADM, CT-proET-1, and hsTNT changed the odds for mortality. Methods A cohort of 53 consecutive patients with septic shock had their levels of MR-proADM, CT-proET-1, hsTNT, and left ventricular systolic functions prospectively measured over 7 days. The relationship between day 1 levels of MR-proADM/CT-proET-1 and myocardial injury was studied. We also investigated the relationship between biomarkers and early (7-day) and later (28-day) mortality. Likelihood ratios, and pretest and posttest odds for mortality were calculated. Results Levels of MR-proADM and CT-proET-1 were significantly higher among patients with myocardial injury and were correlated with left ventricular systolic dysfunction. MR-proADM and hsTNT were significantly higher among 7-day and 28-day non-survivors. CT-proET-1 was also significantly higher among 28-day but not 7-day non-survivors. A positive biomarker panel consisting of the three biomarkers increased the odds for mortality 13-fold to 20-fold. Conclusions MR-proADM and CT-proET-1 are associated with myocardial injury. A biomarker panel combining MR-proADM, CT-proET-1, and hsTNT increases the odds ratio for death, and may improve currently available scoring systems in critical care.